(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Military personnel deployed in high-altitude and extremely cold environments often face challenges in obtaining warm drinking water because electricity, cooking equipment, and open-fire heating methods are not always available. This project aims to develop a portable double-walled self-heating drinking tumbler that provides safe and efficient heating without requiring an external power source. The tumbler consists of an inner stainless-steel chamber for storing drinking water and a separate outer chamber containing a replaceable exothermic heating cartridge. When a small amount of water is added to the heating cartridge, an exothermic reaction generates heat, which is transferred to the beverage through the tumbler wall while preventing direct contact between the heating material and the drinking water. A thermal insulation layer minimizes heat loss, improves energy efficiency, and keeps the outer surface comfortable to hold. The proposed design is lightweight, reusable, leak-proof, corrosion-resistant, and suitable for carrying in military backpacks during long missions. The system is expected to heat beverages to approximately 50–70°C within 10–15 minutes and maintain the desired temperature for an extended period under cold weather conditions. Performance evaluation includes heating efficiency, temperature retention, safety, durability, portability, leakage resistance, and user comfort. The proposed tumbler offers a practical, eco-friendly, and reliable solution for ensuring access to warm beverages in remote locations. In addition to military use, it can benefit trekkers, mountaineers, disaster-response teams, campers, and emergency rescue personnel working in harsh climates where conventional heating methods are unavailable, thereby improving hydration, comfort, health, and operational efficiency.